Progressive changes in crystallographic textures of biominerals generate functionally graded ceramics. Issue 3 (6th January 2022) - Wallis, David; Harris, Joe; Böhm, Corinna F.; Wang, Di; Zavattieri, Pablo; Feldner, Patrick; Merle, Benoit; Pipich, Vitaliy; Hurle, Katrin; Leupold, Simon; Hansen, Lars N.; Marin, Frédéric; et al.
Abstract : Biominerals with gradually-changing crystallographic textures are an unrecognized class of elastically-graded materials that are intrinsically toughened by stress delocalisation. Abstract : Biomineralizing organisms are widely praised for their ability to generate structural materials with exceptional crystallographic control. While earlier studies highlighted near-to single-crystalline biominerals, complex polycrystalline features are more widespread yet challenging to account for. Here, we propose that biominerals whose crystal texture varies with depth are functionally graded materials. Using the exemplary case of the nacro-prismatic pearl oyster Pinctada margaritifera, we demonstrate systematic textural changes in a biogenic ceramic. This bivalve employs three synergistic mechanisms to generate a texture gradient across its outer calcitic shell layer. This prismatic layer transitions from an initially weakly-textured to a strongly-textured material. Such changes in texture cause a variation in Young's modulus normal to the shell, owing to the anisotropic mechanical properties of the composing crystallites. Based on finite-element simulations and indentation experiments on the bivalve shell, we conclude that such graded bioceramics yield intrinsic toughening properties similar to those found in compositionally-graded synthetic materials. Notwithstanding, the gradation concept of Pinctada margaritifera is unparalleled among synthetic materials as it rests solely upon elastic anisotropy, making oyster shells potential blueprints for future bioinspired functional materials and damage-resistant ceramics.